FINANCIAL REPORT ANALYSIS OF PT SAMCRO HYOSUNG ADILESTARI TBK - Rina Maulida; Nada Fitria; Risya Irnanda; Boy Sland Lase; Rico Nur Ilham (Universitas Efarina, 2025)
Study This aim For evaluate performance PT Samcro Hyosung Adilestari's finances Tbk in 2024 through​ analysis ratio finances which include ratio liquidity, solvency, profitability, activity, and market ratios. The data used is secondary data from report finance public companies​ after company official listed on the Indonesia Stock Exchange in January 2024. The results of the analysis show that company is at in condition liquid with current ratio of 1.40 and quick ratio of 1.07, which reflects ability Good in fulfil obligation term short . The Company's solvency level is assessed healthy , reflected from Debt to Asset Ratio of 21.34% and Debt to Equity Ratio of 21.34% of 0.27. In this case profitability , company capable maintain efficiency and generate good profit margins​ with a Gross Profit Margin of 47.04%, Net Profit Margin of 20.84%, ROA of 3.73%, and ROE of 4.74%. However , the performance ratio activity show suboptimal utilization of assets , especially in turnover inventory reaching 256 days and period​ billing receivables that reach 85 days. In general overall, the company own foundation financially strong, but​ need increase effectiveness management asset as well as efficiency operational .